2012
DOI: 10.1080/03079457.2012.660132
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the replication and transmissibility of two infectious laryngotracheitis virus chicken embryo origin vaccines delivered via drinking water

Abstract: Infectious laryngotracheitis (ILT) is an acute infectious viral disease that affects chickens, causing respiratory disease, loss of production and mortality in severe cases. Biosecurity measures and administration of attenuated viral vaccine strains are commonly used to prevent ILT. It is notable that most recent ILT outbreaks affecting the intensive poultry industry have been caused by vaccine-related virus strains. The purpose of this study was to characterize and compare viral replication and transmission p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, three out of the four ILT vaccines used in Algeria are live strains (CHP50, Serva, Hudson), all of which are CEO; only one is a vector vaccine. In fact, CEO vaccines can propagate and recover their virulence after limited back passages between poultry farms [27][28][29]. Many molecular and epidemiological studies confirm that some outbreaks of ILT are caused by CEO vaccines, contrary to the TCO vaccine, which has a low ability to disseminate, and therefore less chance of regaining virulence [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, three out of the four ILT vaccines used in Algeria are live strains (CHP50, Serva, Hudson), all of which are CEO; only one is a vector vaccine. In fact, CEO vaccines can propagate and recover their virulence after limited back passages between poultry farms [27][28][29]. Many molecular and epidemiological studies confirm that some outbreaks of ILT are caused by CEO vaccines, contrary to the TCO vaccine, which has a low ability to disseminate, and therefore less chance of regaining virulence [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CEO vaccines can propagate and recover their virulence after limited back passages between poultry farms [27][28][29]. Many molecular and epidemiological studies confirm that some outbreaks of ILT are caused by CEO vaccines, contrary to the TCO vaccine, which has a low ability to disseminate, and therefore less chance of regaining virulence [27][28][29]. The only TCO vaccine currently produced is the LT-Ivax; it is used only in the USA and Europe [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 100% transmission of Serva vaccine strains was reported by 8 dpe for in-contact birds housed with birds infected via drinking water and eye drop [ 22 ]. In another study, Coppo et al [ 21 ] reported 50–100% transmission of Serva to in-contact birds between 4–8 dpe while only 25% of birds in-contact with SA2 birds inoculated via drinking water became infected by 12 dpe [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coppo et al . (11) reported a more rapid increase in viral genome copies in tracheal swabs of birds vaccinated with SA2 via drinking than those vaccinated with Serva, while the Serva vaccine was transmitted to in-contact birds faster than was SA2. Following airborne exposure of birds (without direct physical contact), the Serva vaccine virus was transmitted to all exposed birds by 17 days postexposure (DPE); while the A20 vaccine virus was transmitted to only 27% of exposed birds at 21 DPE (12).…”
mentioning
confidence: 99%
“…Due to the differences in replication and transmission potential between the Australian A20 and the international Serva ILT vaccines (11,12), there may be variations in the levels of protection provided in partially vaccinated flocks. In light of this, the overall purpose of this study was to determine if the findings of the previous study with the A20 vaccine (13) extend also to the Serva vaccine, one of the most used vaccines in Australian broiler farms and also widely used internationally.…”
mentioning
confidence: 99%